Современная форма научной рациональности - Товарниченко, В.А. (Культура народов Причерноморья, 2003)
В статье проводится сравнительный анализ рациональности классической науки и науки вплоть до середины ХХ века с рациональностью современных научных технологий. Показано возрастание роли науки и научной рациональности в современной культуре, проникновение критериев современной научной рациональности в соседние области в новой форме, в виде компьютерной рациональности. The article is devoted to the camparative analisis of classic science up to the middle of the XX century from one hand and of rationality of modern scientific technologies from another. It’s shown in the article that rising of the role of science and scientific rationality in modern culture is connected with the penetration of the criteria of modern scientific rationality into another spheres in the new forms, first of all, as computer rationality.